Congruence of physics curriculum with decision-making skills requirement for safe seafaring - Jordan, Omar B. (2006)
This study aimed to evaluate the congruency of the Physics curriculum of the Asian Institute of Maritime Studies with the decision-making skills requirement for safe seafaring. Twelve respondents answered the questionnaires that used classifications of causes of maritime accidents. Two Physics classes were also observed and faculty members interviewed. Modal answers were considered as the decisions and required decision-making skills for safe seafaring. Results showed that Physics-related decision-making skills have weak congruence with the competencies specified in the AIMS' Instructor's Guide, CHED syllabus, and international standards. Integration of decision-making skills development is not evident in the implemented and achieved curricula. The Physics curricula should be improved so it could be used for safe seafaring.
"May 2006."
Thesis (M. A. Education : Physics Education)--University of the Philippines, Diliman.
Keywords: Physics -- Study and teaching (Higher) -- Philippines